2017
DOI: 10.1080/10803548.2017.1368950
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals found in the breathing zone, toenails and lung function of welders working in an air-conditioned welding workplace

Abstract: Welding operations are rarely conducted in an air-conditioned room. However, a company would set its welding operations in an air-conditioned room to maintain the humidity level needed to reduce hydrogen cracks in the specimen being welded. This study intended to assess the exposure to metal elements in the welders' breathing zone and toenail samples. Heavy metal concentration was analysed using inductively coupled plasma mass spectrometry. The lung function test was also conducted and analysed using statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…However, direct comparison of Mn exposure levels is not possible given that the studies of welders measured Mn in blood and we measured Mn in hair and toenails. Notably, hair and toenail Mn concentrations in our study were lower than those reported in previous occupational and environmental studies (Table S9) (Grashow et al, 2014;Hariri et al, 2018;Hassani et al, 2016;Mora et al, 2014;Ohgami et al, 2018;Reiss et al, 2016;Rodrigues et al, 2015;Rolle-McFarland et al, 2018;Ward et al, 2017), though it is unclear if these differences are real or due to variations in the cleaning procedures used to prepare the biological samples for analysis.…”
Section: Discussioncontrasting
confidence: 87%
“…However, direct comparison of Mn exposure levels is not possible given that the studies of welders measured Mn in blood and we measured Mn in hair and toenails. Notably, hair and toenail Mn concentrations in our study were lower than those reported in previous occupational and environmental studies (Table S9) (Grashow et al, 2014;Hariri et al, 2018;Hassani et al, 2016;Mora et al, 2014;Ohgami et al, 2018;Reiss et al, 2016;Rodrigues et al, 2015;Rolle-McFarland et al, 2018;Ward et al, 2017), though it is unclear if these differences are real or due to variations in the cleaning procedures used to prepare the biological samples for analysis.…”
Section: Discussioncontrasting
confidence: 87%
“…Welding is one of the basic processes in many industries in which metals or thermoplastic materials are joined together using heat, pressure or both (Hariri et al 2018). Estimates shows, in 2011, approximately 316000 welders had been busy working in united states; They mainly worked in soldering, welding, brazing, and cutting process (Barkhordari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During the welding process, hazardous chemical compounds are released in the forms of gas, fume, and vapor (Hariri et al 2018). Generated welding fumes have a complex composition (Persoons et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Once in the body, THM affect different physiological processes, even at very low concentrations [ 6 ], as they are used as a substitute of essential elements: Pb can take the place of calcium and Cd the place of Zn [ 7 ]. As a result, they can cause numerous diseases, such as kidney toxicity [ 8 ], impaired lung function [ 9 ], neurotoxic effects [ 10 , 11 ], hormonal imbalance [ 12 ], abnormal spermatogenesis and infertility [ 13 ], and even cancer [ 14 , 15 , 16 ]. Furthermore, THM can cross the placenta and interfere with fetal developmental processes [ 17 ].…”
Section: Cadmium: the Beginning Of History In Humansmentioning
confidence: 99%